Estimated Glomerular Filtration Rate Increases in Chronic Hepatitis B Patients Treated With Telbivudine Monotherapy and Combination Treatment - Jiang, Libin (Hepat Mon, 2016)
BACKGROUND: Several studies have reported a renoprotective effect of telbivudine during the treatment of patients for chronic hepatitis B (CHB). OBJECTIVES: This longitudinal retrospective study aimed to examine the effects of telbivudine monotherapy and combination therapy (adefovir plus telbivudine) on renal function. PATIENTS AND METHODS: This study included 336 Chinese CHB patients, who were selected from outpatients in Tongji Hospital. 44, 122, 66, 58, and 46 of these patients had been orally taking adefovir, telbivudine, entecavir, adefovir plus telbivudine, and adefovir plus lamivudine, respectively, for at least 24 months. RESULTS: The estimated glomerular filtration rate (eGFR) in the telbivudine and adefovir plus telbivudine groups increased by 5.14 mL/min (P < 0.001) and 6.19 mL/min (P = 0.005), respectively. The patients taking the five drug regimens were further grouped into the following three subpopulations: those with compensated hepatic cirrhosis, those aged 50 or more years, and those with baseline eGFR values of 50 - 90 mL/min. The three subgroups that received telbivudine monotherapy exhibited eGFR increases of 6.38, 6.74, and 10.82 mL/min, respectively. The three subgroups that received combination therapy of adefovir plus telbivudine exhibited eGFR increases of 18.31, 14.73, and 16.59 mL/min, respectively (P < 0.05). The predictive factors for the change in eGFR levels over time were analyzed by means of two linear mixed effects models for the three monotherapy regimens and two combination regimens. Age, gender, and medication are predictive factors of eGFR changes. In addition, abnormal creatinine kinase (CK) levels in the telbivudine group were not correlated with eGFR changes (P = 0.992). CONCLUSIONS: These findings indicate that telbivudine, used in both monotherapy and combination therapy, improves the renal function of patients with CHB. The improvements are particularly significant in patients at high renal risk.